The effect of metformin in clinical studies on knee osteoarthritis: an updated systematic review and meta-analysis - Guo, Xiaoqi; Xie, Haibin; Liu, Yuanfan; Hou, Jianye; Tan, Haochen; Miao, Lin; Xu, Ying; Tian, Ye (Frontiers in Medicine, 2025)
ObjectivesMetformin is regarded as a potential drug for the treatment of knee osteoarthritis (KOA), but its efficacy remains unclear. This systematic review and meta-analysis aims to evaluate the efficacy of metformin in the treatment of KOA.MethodsAccording to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we searched three literature databases, including PubMed, Web of Science and EMBASE, and conducted a systematic review and meta-analysis of randomized controlled trials and cohort studies up to April 1, 2025, studies evaluating the use of metformin in the treatment of KOA were included. Hazard ratio (RR), standard mean difference (SMD), and the corresponding 95% confidence interval (CI) were used as aggregated statistics. This systematic review is registered on RROSPERO (CRD420251026750).ResultsA total of six eligible studies included 4,628 patients (1,489 patients use metformin versus 3,139 patients non-use). The main observation outcome was the score of the pain scale (WOMAC, KOOS, VAS, etc.) of the knee joint and the incidence of total knee arthroplasty (TKA) is a secondary outcome. Analysis of the included population the included population reveals that the BMI levels of all individuals were at the overweight range. In this situation, the comprehensive results show that regardless of different conventional treatment methods, courses of treatment and doses, combined metformin treatment in the incidence of joint replacement [RR = 0.65, 95% CI (0.54, 0.77), p < 0.00001] and knee pain scores [SMD = −0.47, 95% CI (−0.84, −0.11), p = 0.01], it was superior to the control group treatment.ConclusionThe research results show that metformin can relieve the pain of KOA with high BMI and reduce the possibility of joint replacement. However, due to the less of randomized controlled trials (RCTS), clinicians should be fully cautious when using it.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251026750.